Myths of Ancient Greece and Rome in didactics - Głogowska, Katarzyna (Collectanea Philologica, 2016)
In text below the author would like to take this opportunity to raise the issue of the possibility of presenting during Latin lessons wide range of information relating to the myths and legends of Ancient Greece and Rome. A lesson dedicated to the Olympian gods will serve as an example of such practice. This lesson will provide a starting point for students and it will enable them to meet the fascinating world of history and culture of the classical antiquity. This article will start with presentation of the most important information about the polish school ‘gimnazjum’ and the curriculum of the Latin language in this school. Then some formal issues connected with conducting the discussed lesson will be highlighted. Afterwards the original lesson plan will be discussed. During the lesson the selected canon of Greek and Roman myths will be presented and then enriched by multimedia presentation and additional exercises. In addition to this both the lesson objectives and teaching methods and forms of work will be shown. Nowadays, very important matter is that all of this should be achieved in a friendly manner and at the same time it should be clear and understandable for pupils, who take Latin classes. This is a real challenge, it is a really difficult task to gain interest of those young people, who are accustomed or even addicted to the use of the Internet, in the language such as Latin. In addition, the author would like to show the pupils the timeless value of myths and legends of the classical antiquity and draw their attention to rediscover the power of classical myths, symbols and concepts in the 21st century.